MoTe2 quantum dot ink synthesized by two-step liquid phase stripping method and preparation method of near-infrared detector of MoTe2 quantum dot ink
The synthesis of MoTe2 quantum dot ink by two-step liquid-phase peeling method solves the interface defect problem in the MoTe2 quantum dot film, significantly improving the device's photoelectric performance, especially the response rate and detection rate at near-infrared wavelengths.
Patent Information
- Application Number
- CN202411624967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-14
AI Technical Summary
In the prior art, when preparing MoTe2 quantum dot films, interface defects are easily introduced, resulting in a decrease in carrier migration rate and a decrease in device performance.
The MoTe2 quantum dot ink was synthesized by a two-step liquid phase peeling method. The specific steps included sonication of MoTe2 powder to prepare nanosheets, followed by sonication in N,N-dimethylformamide solvent to prepare MoTe2 quantum dots, and finally dissolving the quantum dots in isopropanol to prepare ink.
The MoTe2 quantum dot film prepared by this method has good surface flatness, denseness and uniformity, which significantly improves the photoelectric performance of the device, especially the response rate and detection rate at wavelengths of 850nm and 940nm.
Smart Images

Figure CN119592126A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing high-quality MoTe2 quantum dot (QDs) ink and a thin film device, and in particular to the technical field of MoTe2 QDs ink and near-infrared detector preparation. Background Art
[0002] Infrared detectors are widely used in night vision imaging, communications and gas sensing. Molybdenum ditelluride (MoTe2) belongs to transition metal dichalcogenides (TMDs) and is a material with a narrow band gap and high electron mobility in the TMDs family. However, due to its van der Waals structure, the prepared quantum dot devices are currently less studied. Therefore, the preparation and performance research of devices based on this material is of great significance to the development of photoelectric detection devices.
[0003] MoTe2 is a popular low-toxic two-dimensional semiconductor material in the field of near-infrared detectors. The thin film made of it is often the most critical part of the detector. However, there are no reports on near-infrared detectors using MoTe2QDs. Preparing MoTe2 into quantum dot ink in a top-down manner and then spin-coating it into a thin film as the photosensitive layer of near-infrared detectors is conducive to the expansion of MoTe2 quantum dots in the field of optoelectronic applications.
[0004] The preparation of MoTe2 QDs thin film by spin coating MoTe2 ink will introduce interface defects, which will cause carrier recombination during transportation due to the existence of defects, reduce the carrier migration rate, and reduce the performance of the device. Therefore, it is particularly important to prepare a thin film with smooth surface, good density and uniformity. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing MoTe2 quantum dot ink and its near-infrared detector by a two-step liquid phase exfoliation method to solve the problems existing in the background technology. Specifically, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing MoTe2 quantum dot (QDs) ink, comprising the following steps:
[0007] S1: Weigh MoTe2 powder and add it to a condensation beaker filled with N-methyl-pyrrolidone solvent. Ultrasonicate at a power of 300W for 30 hours using an ultrasonic instrument, and then centrifuge to retain the precipitate. Wash the precipitate with acetone for several times, and vacuum dry it to obtain clean MoTe2 nanosheets.
[0008] S2: Add N,N-dimethylformamide to the cleaned MoTe2 nanosheet powder, ultrasonicate at 300W for 30h, centrifuge the mixed solution after ultrasonic treatment at 1000r / min to obtain the supernatant, then centrifuge the supernatant at 8000r / min to obtain the precipitate, add acetone solution to the MoTe2 QDs precipitate, wash 2-3 times to obtain MoTe2 QDs solution, centrifuge and pour off the supernatant, and dry the precipitate to obtain the final MoTe2 QDs powder;
[0009] S3: Add isopropanol solvent to the final MoTe2 QDs powder and shake to dissolve it to obtain MoTe2 QDs ink.
[0010] Furthermore, in step S1, the mass volume ratio of MoTe2 powder and N-methyl-pyrrolidone solvent is 2:50.
[0011] Furthermore, in step S2, the mass volume ratio of MoTe2 nanosheets and N,N-dimethylformamide solvent is 2:50.
[0012] The present invention also provides a method for preparing a MoTe2 QDs film, which comprises the following steps: spin coating the MoTe2 QDs ink obtained by any of the preparation methods to obtain the MoTe2 QDs film.
[0013] Furthermore, the MoTe2 QDs ink obtained by any of the preparation methods described in the present invention is used in the preparation of near-infrared detectors.
[0014] In one embodiment, the present invention provides a method for preparing a near-infrared detector, which prepares a near-infrared detector with a Si-SiO2-Au structure by magnetron sputtering. During the preparation process, a thin film of MoTe2 QDs ink obtained by any preparation method is spin-coated in the middle of a gold electrode to form an Au-MoTe2-Au structure.
[0015] The technical effects achieved by the present invention are:
[0016] The present invention uses quantum dots as the photosensitive layer in the MSM (Metal-Semiconductor-Metal) structure device, and the gold electrodes at both ends are responsible for transmitting electrons and holes. The planar device structure enables it to absorb incident light to a greater extent, and compared with the vertical structure device, it avoids the attenuation effect of the functional layer on the incident light. The maximum response rate and detection rate of the quantum dot device under the irradiation of light with a wavelength of 850nm are 0.13A / W and 2.4×10 10 Jones; 0.05A / W and 8×10 9 Jones, this result provides a strategy for the application of MoTe2 quantum dots in optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 .Preparation and TEM images of MoTe2: (a) MoTe2 QDs preparation flow chart; (b) MoTe2 QDS device preparation flow chart; (cf) TEM image of MoTe2 nanosheets prepared by NMP ultrasound; (gh) TEM image of MoTe2 QDs prepared by DMF ultrasound;
[0018] Figure 2 .Optical test and device structure characterization of MoTe2 quantum dots. (a) Curve of the relationship between the diameter and band gap of MoTe2 quantum dots, (b) UV-Vis-NIR absorption spectrum of quantum dots, (c) AFM image of MoTe2 quantum dot layer, (d) device structure, (e) cross-sectional SEM image of the device, (f) planar SEM image of the device;
[0019] Figure 3 .The test results of the photoelectric performance of MoTe2: (a) IV diagram of the photodetector of the MoTe2 device under 850nm and 940nm LED light sources; (bd) EQE, R and D* of the MoTe2 device respectively. Specific embodiments
[0020] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0022] Example 1 Preparation of MoTe2 quantum dot ink
[0023] Figure 1 (a) is a flow chart of the preparation of MoTe2 quantum dots by liquid phase exfoliation method, and the specific steps are as follows:
[0024] S1: Weigh 2g of MoTe2 powder and add it to a condensation beaker filled with 50mL of N-methyl-pyrrolidone solvent. Ultrasound is performed for 30h at a power of 300W using a probe ultrasonic instrument. The mixed solution after ultrasonic treatment is centrifuged at 8000r / min for 20min to retain the precipitate. The precipitate is washed with acetone for 2-3 times and vacuum dried to obtain clean MoTe2 nanosheets.
[0025] S2: Add 50 mL of N,N-dimethylformamide to 2 g of clean MoTe2 nanosheet powder, and then use a probe ultrasonicator to sonicate for 30 h at 300 W to obtain a mixed solution of MoTe2 quantum dots and nanosheets. The mixed solution after ultrasonic treatment is centrifuged at 1000 r / min to obtain the supernatant, thereby removing the unbroken MoTe2 nanosheets. The supernatant is then centrifuged at 8000 r / min to obtain a precipitate. Acetone solution is added to the MoTe2 QDs precipitate, washed 2-3 times to obtain a MoTe2 QDs solution, centrifuged and the supernatant is discarded, and the final MoTe2 QDs powder is obtained after drying;
[0026] S3: adding isopropanol solvent to the final MoTe2 QDs powder and shaking to dissolve it to obtain MoTe2 QDs ink;
[0027] S4: The MoTe2 QDs ink solution is spin coated to obtain a MoTe2 QDs thin film.
[0028] Example 2 Preparation of MoTe2 quantum dot devices
[0029] The obtained MoTe2 quantum dot powder was added with isopropanol as a dispersant to prepare 80 mg / mL MoTe2 quantum dot ink for use, and then a near-infrared detector with a Si-SiO2-Au structure was prepared by magnetron sputtering, and a thin film of MoTe2 quantum dot ink was spin-coated in the middle of the gold electrode.
[0030] The specific steps are:
[0031] S1: The silicon wafer was ultrasonically cleaned in acetone and deionized water for 30 min respectively;
[0032] S2: A 300nm thick SiO2 film is deposited on the front side of the silicon wafer by magnetron sputtering technology;
[0033] S3: Place the mask on the coated SiO2 film, and then use magnetron sputtering technology to sputter a 50nm gold electrode on the SiO2 surface;
[0034] S4: Spin-coat the MoTe2 QDs solution in the middle of the gold electrode;
[0035] S5: Paste the spin-coated electrodes on the circuit board, and use silver paste to lead out gold wires from the two electrodes on the surface of the sample. The other end of the gold wires is soldered to the circuit board. Then, connect the load circuit from the corresponding pins to test its response characteristics.
[0036] Effect
[0037] Figure 1(a) is a schematic diagram of the preparation of quantum dots by liquid phase exfoliation. NMP (N-methyl-pyrrolidone) is mainly used to destroy the van der Waals force between the layers of MoTe2 materials during the ultrasonic process, thereby preparing MoTe2 few-layer nanosheets with a lateral size of 100-200nm. DMF (N,N-dimethylformamide) is then used to break the covalent bonds between Te and Mo between the MoTe2 nanosheets during the ultrasonic process. The entire process is carried out in a cooling circulating water cup to ensure the constant experimental temperature. Finally, MoTe2 quantum dots with an average particle size of 3.5nm are obtained. Finally, the quantum dot powder is dried at 50 degrees in a vacuum drying oven, and isopropanol solvent is used as a dispersant to prepare MoTe2 quantum dot ink with a concentration of 80mg / mL. Figure 1 (b) SiO2 and Au are sputtered layer by layer on a silicon wafer by magnetron sputtering, and finally MoTe2 quantum dot ink is spin-coated on the interdigital electrodes of the Si-SiO2-Au structure. Figure 1 (cf) is a TEM image of MoTe2 nanosheets obtained after using NMP ultrasound for 30 hours on MoTe2 powder. Figure 1 In (c), it can be seen that the lateral size of the nanosheets is between 100 and 300 nm, indicating that the ultrasonic exfoliation of the nanosheets by NMP is highly efficient; Figure 1 (d) is the TEM diffraction pattern of the nanosheet. The marked diffraction points correspond to the (0 0 8), (1 0 0), (1 0 8), and (2 0 8) crystal planes of the MoTe2 material. The arrows from the transmission center to the diffraction spots can also represent vectors, which satisfy the geometric properties of vectors in the diffraction space. The geometric vector formed by (0 0 8) and (1 0 0) corresponds to the (1 0 8) crystal plane, and the geometric vector formed by (1 0 0) and (1 0 8) corresponds to the (2 0 8) crystal plane. Figure 1 (e) is a TEM scan of the van der Waals layer on the side of a thicker MoTe2 nanosheet, with an interlayer spacing of 0.7nm, and each layer is composed of alternating Te and Mo atomic structures; Figure 1 (e) is a TEM scan of a thicker MoTe2 nanosheet plane, which is composed of Te and Mo atoms alternating in a regular hexagonal structure; Figure 1 (f) is a TEM image of MoTe2 quantum dots obtained by DMF ultrasound. From the inserted particle size distribution diagram, it can be seen that the average particle size (Xc) is 3.5nm and the half-peak width (FWHM) of the size distribution of quantum dots is 1.3nm, indicating that this method is feasible for preparing MoTe2 quantum dots. Figure 1 (d) is a high-resolution transmission electron microscopy (HRTEM) image of quantum dots, from which it can be clearly seen that they have a high degree of crystallinity and the presence of (0 0 8) and (1 0 5) crystal planes, indicating that the ultrasonic process did not destroy the crystal structure of MoTe2.
[0038] The relationship between the band gap and size of MoTe2 QDs can be calculated using the following formula:
[0039]
[0040] E in formula 1 g is the body band gap of MoTe2 material (0.88 eV), m e is the effective mass of the electron (m e =0.34m0), m h is the effective mass of the hole (m h =0.48m0), m o =9.11×10 -34 F / m, ε0 is the dielectric constant of vacuum (8.854×10 -12 F / m), ε r is the relative dielectric constant of MoTe2 (13), e is the electron charge, and R is the radius of the quantum dot;
[0041] Figure 2 (a) is the particle size and band gap variation curve of MoTe2 quantum dots obtained by formula 1. The bulk band gap of MoTe2 is 0.88eV (marked with a red dotted line in the figure). When the size of the quantum dots is very small, the band gap is very large, exceeding 3eV. This is because the quantum dot size is too small, and the quantum effect produced is extremely large. The band gap decreases with the increase of radius, until it exceeds the exciton Bohr radius, and this quantum effect is almost non-existent. This leads to the fact that the band gap of the quantum dot has almost no size correlation after the size of the quantum dot is greater than 4nm, and the size is close to the bulk band gap. This means that when the diameter changes within 4nm, the material will have a strong quantum size effect, which further shows that the experimental preparation of 3.5nm MoTe2 quantum dots will produce strange quantum effects. Figure 2 (b) is the UV-Vis-NIR absorption spectrum of MoTe2 quantum dots spin-coated on quartz. From the figure, we can see that its absorption covers the visible near-infrared band. The body band gap of the material is 0.88eV. When it becomes a quantum dot structure, the band gap will increase. From the exciton peak at 1150nm in the figure, it can be roughly concluded that the band gap of the MoTe2 quantum dot structure is 1.10eV. Figure 2 (c) is a planar atomic force microscope (AFM) image of the quantum dot film, which shows that the surface roughness of the film is 12nm and the surface is relatively flat; Figure 2 (d) is a physical picture of MoTe2 quantum dot device; Figure 2 (e) is a cross-sectional scanning electron microscope (SEM) image of the interdigitated electrode. From bottom to top, we can see Si, SiO2 and MoTe2 quantum dot layers, respectively. The MoTe2 quantum dot layer serves as a photosensitive layer with a thickness of about 260 nm and a smooth film thickness. Figure 2(f) is a planar SEM image of a near-infrared detector without spin-coating of MoTe2 quantum dots. The gold part represents the gold electrode, and the black area in the middle represents the channel, whose channel width is less than 1 μm.
[0042] Figure 3 (a) is the IV graph of the MoTe2 near-infrared detector under 850nm and 940nm LED light sources. It can be seen that the device has a certain response to near-infrared light and has a greater response to 850nm light, which is related to the optical absorption of the material; Figure 3 (bd) are the EQE, R and D* of the device in the range of -1V to 1V bias calculated by IV curves. When irradiated with light of wavelengths of 940nm and 850nm, EQE reaches its maximum value at -1V, which are 0.18 and 0.50, respectively. R is 0.05A / W and 0.14A / W at -1V, respectively. D* reaches 8×10 9 Jones and 2.4×10 10 Jones
[0043] In summary, the present invention uses NMP solvent and DMF solvent step-by-step ultrasonic liquid phase exfoliation method to prepare MoTe2 quantum dots with an average size of 3.5nm, and disperses them in isopropanol to prepare quantum dot ink. By spin coating, MoTe2 is used as the photosensitive layer material of Au-MoTe2-Au near-infrared detector. The iv curve of the device under different wavelengths of light shows that the maximum response rate and detection rate of the quantum dot device under 850nm wavelength light are 0.13A / W and 2.4×10 10 Jones; 0.05A / W and 8×10 9 Jones. This indicates that MoTe2 has great application prospects in the field of photoconductive near-infrared detectors. In subsequent studies, improving the flatness of the MoTe2 film surface may enable the application of this quantum film in vertical structure junction detectors.
Claims
1. A method for preparing MoTe2 quantum dot (QDs) ink, characterized in that: The steps include: S1: Weigh MoTe2 powder and add it to a condensation beaker filled with N-methyl-pyrrolidone solvent. Ultrasonicate at 300W power for 30 h, then centrifuge to retain the precipitate. Wash the precipitate with acetone for several times, and vacuum dry to obtain clean MoTe2 nanosheets. S2: Add N,N-dimethylformamide to the clean MoTe2 nanosheet powder, ultrasonicate at 300W for 30h, centrifuge the mixed solution after ultrasonic treatment at 1000 r / min to obtain the supernatant, then centrifuge the supernatant at 8000 r / min to obtain the precipitate, add acetone solution to the MoTe2 QDs precipitate, wash 2-3 times to obtain MoTe2 QDs solution, centrifuge and pour off the supernatant, and dry the precipitate to obtain the final MoTe2 QDs powder; S3: Add isopropanol solvent to the final MoTe2 QDs powder and shake to dissolve it to obtain MoTe2 QDs ink.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass volume ratio of MoTe2 powder and N-methyl-pyrrolidone solvent is 2:
50.
3. The preparation method according to claim 1, characterized in that: In step S2, the mass volume ratio of MoTe2 nanosheets and N,N-dimethylformamide solvent is 2:
50.
4. A method for preparing a MoTe2 QDs film, characterized in that: The MoTe2 QDs thin film is obtained by spin coating the MoTe2 QDs ink obtained by any preparation method described in claims 1-3.
5. Use of the MoTe2 QDs ink obtained by any preparation method described in claims 1-3 in the preparation of near-infrared detectors.
6. A method for preparing a near-infrared detector, preparing a near-infrared detector of Si-SiO2-Au structure by magnetron sputtering, characterized in that: During the preparation process, a thin film of the MoTe2 QDs ink obtained by any preparation method of claims 1-3 is spin-coated in the middle of the gold electrode to form an Au-MoTe2-Au structure.
Citation Information
Patent Citations
Ultrasonic liquid phase stripping preparation method for big production antimonene quantum dots
CN107234244A
Negative temperature coefficient (NTC) thermistors utilising transition metal dichalcogenide quantum dots
US20230207161A1
Exfoliation of layered materials
WO2012101457A1
Megasonically exfoliated two-dimensional nanomaterial INKS, fabricating methods, and applications of the same
WO2023239539A1
Dispersion liquid, photoelectric conversion film, method for producing photoelectric conversion film, photodetection element and image sensor
WO2024166697A1